AN ANALYSIS OF MEDIA BASED LEARNING USED BY TEACHER AT MTS ALAZHAR CENTER BATURAJA DURING PANDEMIC COVID-19 - Sena Maritin; Mila Arizah; Nurul Afifah (Journal of Language Education (JoLE), 2021)
This research aims to determine English teacher of media based learning at MTs al azhar center Baturaja during pandemic covid-19. This research used descriptive qualitative case study. The subject of this research were two teachers majoring in English at MTs al azhar center Baturaja. The data was collected through the direct in interview with the teacher. The result of this study are the teachers have used media based learning such as Google classroom in very well. The teacher used Google classroom they think is very effective. google classroom can make the teacher challenge their self to be more productive to give knowledge for students. Google classroom useful for the teacher, the teacher can use many features such as class assignment features, material features and questions features. The teacher can connect google classroom in HP, laptop or computer so the teacher don’t need more time to teach the students. The teacher also increases student motivation because students easily send assignment and get materials. There are two challenge factors in using google classroom. The first is facility factor and the second is the student factor. Teachers provide an alternative in the form of using a white board if there are obstacles such as internet access . then, students also sometimes have to find alternative networks such as wifi to send assignments.